Effect of methamphetamine on cognitive functions of adult female rats prenatally exposed to the same drug - Macúchová, E; Nohejlová-Deykun, K; Slamberová, R (Physiological research, 2013)
The aim of this study was to investigate the effect of prenatal methamphetamine (MA) exposure and application of the same drug in adulthood on cognitive functions of adult female rats. Animals were prenatally exposed to MA (5 mg/kg) or saline (control group). The cognitive function was tested as ability of spatial learning in the Morris Water Maze (MWM). Each day of the experiment animals received an injection of MA (1 mg/kg) or saline. Our results demonstrated that prenatal MA exposure did not affect the latency to reach the hidden platform or the distance traveled during the Place Navigation Test; however, the speed of swimming was increased in prenatally MA-exposed rats compared to controls regardless of the treatment in adulthood. MA treatment in adulthood increased the latency and distance when compared to controls regardless of the prenatal exposure. Neither prenatal exposure, nor treatment in adulthood affected memory retrieval. As far as the estrous cycle is concerned, our results showed that prenatally MA-exposed females in proestrus/estrus swam faster than females in diestrus. This effect of estrous cycle was not apparent in control females. In conclusion, our results indicate that postnatal, but not prenatal exposure to MA affects learning of adult female rats.
Keywords: Rats; Animals, Newborn; Cognition; těhotenství; sexuální faktory; Cognition Disorders; Rats, Wistar; novorozená zvířata; Maze Learning; Central Nervous System Stimulants; krysa rodu Rattus; kognitivní poruchy; kognice; ženské pohlaví; zvířata; methamfetamin; Pregnancy; Sex Factors; zpožděný efekt prenatální expozice; stimulanty centrálního nervového systému; potkani Wistar; Methamphetamine; Female; bludiště - učení; Prenatal Exposure Delayed Effects; Animals